2013
DOI: 10.1097/jom.0b013e318291787a
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Prolonged QT Interval on Electrocardiography and Chronic Lead Exposure

Abstract: The data suggest that lead exposure is positively associated with prolonged QTc interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…Although many studies have documented that lead exposure is associated with ischemic heart disease, HT, and cerebrovascular accident, cardiac conduction tissue can also be affected leading to conduction abnormalities and arrhythmias. In a study from Taiwan, Chen et al found that workers exposed to lead occupationally had significantly shorter PR interval and longer QTc interval compared with controls. Furthermore, no significant relationship of blood lead level was observed with PR interval, whereas there was a significant relationship with QTc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have documented that lead exposure is associated with ischemic heart disease, HT, and cerebrovascular accident, cardiac conduction tissue can also be affected leading to conduction abnormalities and arrhythmias. In a study from Taiwan, Chen et al found that workers exposed to lead occupationally had significantly shorter PR interval and longer QTc interval compared with controls. Furthermore, no significant relationship of blood lead level was observed with PR interval, whereas there was a significant relationship with QTc.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few relevant studies investigating the effects of lead on the cardiac conduction system. In these studies, the relationship between lead exposure and electrocardiographic parameters such as QT interval, QRS duration and conduction disturbances have been investigated …”
mentioning
confidence: 99%
“…Cardiovascular diseases are the leading cause of mortality both in the United States and around the world [ 1 ]. Exposure to lead potentially accelerates the development of several cardiovascular diseases or disorders such as coronary heart disease, peripheral arterial disease, left ventricular hypertrophy, and cardiac arrhythmias in acute and chronic exposure [ 2 , 3 , 4 , 5 ]. Indeed, lead is a risk factor for hypertension in adults, and a positive association of lead exposure with elevated blood pressure has also been identified in the literature [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…QTc interval is referred to as the period of ‘electrical systole’ of the ventricles 10. This duration prolongs when the heart rate shortens.…”
Section: Discussionmentioning
confidence: 99%